Cost Analysis of Adjunctive Hydrocortisone Therapy for Septic Shock: U.S. Payer Perspective. Issue 10 (October 2020) - Oh, Mok; Patanwala, Asad E.; Alkhatib, Nimer; Almutairi, Abdulaali; Abraham, Ivo; Erstad, Brian
Abstract : Objectives: To conduct a cost analysis of adjunctive hydrocortisone therapy for severe septic shock from the perspective of a third-party payer in the United States. Design: Estimates of outcomes were aggregate data from the Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock and Activated Protein C and Corticosteroids for Human Septic Shock trials. In these trials, the outcomes of interests were ICU length of stay, vasopressor-free days, ventilation-free days, and the proportion of patients receiving blood transfusion. Each outcome was monetized into a set of mutually exclusive components and was aggregated to estimate the cost-per-patient based on each trial. Cost inputs for each outcome were obtained from literature and adjusted based on the medical care consumer price index. To estimate the budget impact using adjunctive hydrocortisone therapy, per-patient avoided cost was multiplied by expected septic shock annual incidence. Deterministic one-way sensitivity analysis evaluated the robustness of the findings, and Monte Carlo simulation estimated 95% CI of the findings. Setting: A total of 103 medical-surgical ICU (69 for Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock and 34 for Activated Protein C and Corticosteroids for Human Septic Shock). Patients: Adults greater than or equal to 18 years old with septic shock. Interventions: Adjunctive hydrocortisone therapy (hydrocortisone at a dose of 200 mg/d for 7 d for Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock and hydrocortisone at a 50 mg IV bolus every 6 hr and fludrocortisone as a 50 μg tablet once daily). Measurements and Main Results: Per Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock, adjunctive hydrocortisone therapy showed a 90-day monetized benefit of $8, 111 (95% CI, $3, 914–$12, 307) per patient, driven by improvements in ICU-free days, vasopressor-free days, ventilation-free days, and blood transfusion proportion. The total estimated annual impact of adjunctive hydrocortisone therapy, in 2019 dollars, was $750 million. Per Activated Protein C and Corticosteroids for Human Septic Shock, adjunctive hydrocortisone therapy showed a 90-day monetized benefit of $25, 539 per patient (95% CI, $22, 853–$28, 224), driven by improvements in ICU free-days, vasopressor-free days, and ventilation-free days. The total estimated annual impact of adjunctive hydrocortisone therapy, in 2019 dollars, was $2.3 billion. The deterministic one-way sensitivity analysis showed the cost of ICU stays to be the most influential factor in both analyses. The sensitivity analysis using the reported median showed a greater monetized benefit of $10, 658 (Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock) and $30, 911 (Activated Protein C and Corticosteroids for Human Septic Shock) per patient. Conclusions: Using adjunctive hydrocortisone therapy yields a significant monetized benefit based on inputs from the Adjunctive Corticosteroid Treatment in Critically Ill Patients with Septic Shock and Activated Protein C and Corticosteroids for Human Septic Shock trials.